مقومات الاستثمار في القطاع السياحي بولايات الجنوب الغربي والهضاب العليا في الجزائر " مع الاشارة لولايتي بشار وتيسمسيلت - العرابي, عبدالغني; عريس, مختار (جامعة الوادي - University of Eloued, 2023)
This research paper aims to shed light on the reality of investment in the desert tourism sector and the high plateaus, and its role in improving the rates of social life, with reference to the wilayas of Bechar and Tissemsilt in particular, as the first is a desert state, and the second is one of the wilayas of the high plateaus. By collecting up-to-date information from various sources. After an overview of the structure of the tourism sector and tourism investments, the most important qualifications of the tourism offer in the two states were presented. We adopted the inductive approach through the description and analysis of the tourism sector in these two states. It was concluded that desert tourism in Algeria is still, despite all efforts, traditional tourism, with many deficiencies recorded at the level of infrastructure and tourist facilities.
The Investment components for the tourism sector inside the states of the south-west and the high plateaus in Algeria - with referenceto the states of Bechar and Tissemsilt
مقال
Keywords: سياحة، استثمار، تنمية، اقتصاد جزائري، ولاية بشار ، ولاية تيسمسيلت; :tourism, investment, development, Algerian economy, Bechar, Tessemsilt